The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.5901/mjss.2015.v6n1s1p560
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fuel Price Increaseon the Nigerian Economy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The analysis of result of questionnaire validity and reliability showed high reliability and this is supported by Hinton et al (2004), Straub et al (2004) and Feng and Yamat (2019). Changes in prices of petrol rice and bean in Nigeria have continued to attract widespread attention (Ocheni, 2015;Orlu, 2017;Nwosu et al, 2016).The consumption pattern of petrol, rice and bean has faced dramatic changes even in recent times and therefore estimates of how their consumption is affected by changes in price is necessary (Dunnem and Edkins, 2005). Hike in the prices of petrol, rice and bean could incontrovertibly lead to food security problems and poverty.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of result of questionnaire validity and reliability showed high reliability and this is supported by Hinton et al (2004), Straub et al (2004) and Feng and Yamat (2019). Changes in prices of petrol rice and bean in Nigeria have continued to attract widespread attention (Ocheni, 2015;Orlu, 2017;Nwosu et al, 2016).The consumption pattern of petrol, rice and bean has faced dramatic changes even in recent times and therefore estimates of how their consumption is affected by changes in price is necessary (Dunnem and Edkins, 2005). Hike in the prices of petrol, rice and bean could incontrovertibly lead to food security problems and poverty.…”
Section: Resultsmentioning
confidence: 99%
“…Instability in the price of petrol, rice and bean disorganises many Nigerian households, causes disorderliness in the feeding pattern of the people and ultimately impoverishes the citizenry. Evidences (Ocheni, 2015;Orlu, 2017) have shown that when the price of petrol increases, even when it is marginal, cost of transportation becomes too exorbitant. This in turn affects every other activity in the country and prices of other commodities including rice and bean become adversely affected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the survey research design, (Ocheni, 2015) discovered that PMS Price hiking reduces the purchasing power of the Nigerian naira but increased food security. Again, the researcher traced the slow economic propensity of Nigeria to oil sector performance to PMS Price hiking.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…That is, there should be a simultaneous development of various sectors of the economy instead of overreliance on a particular sector of the economy (mono production-based economy). In Nigeria, almost all other sectors of the economy seem to have gone into oblivion, thereby, making the country to depend almost entirely on crude oil for her foreign exchange (Ocheni 2015). In this respect, the expansion of export-base commodities is of tremendous importance to the overall development of the economy (Awe and Ajayi 2009;Bala 2015).…”
Section: Introductionmentioning
confidence: 99%